Pro-Inflammatory wnt5a and Anti-Inflammatory sFRP5 Are Differentially Regulated by Nutritional Factors in Obese Human Subjects - Schulte, Dominik M.; Müller, Nike; Neumann, Katrin; Oberhäuser, Frank; Faust, Michael; Güdelhöfer, Heike; Brandt, Burkhard; Krone, Wilhelm; Laudes, Matthias (PloS one, 2012)
Obesity is associated with macrophage infiltration of adipose tissue. These inflammatory cells affect adipocytes not only by classical cytokines but also by the secreted glycopeptide wnt5a. Healthy adipocytes are able to release the wnt5a inhibitor sFRP5. This protective effect, however, was found to be diminished in obesity. The aim of the present study was to examine (1) whether obese human subjects exhibit increased serum concentrations of wnt5a and (2) whether wnt5a and/or sFRP5 serum concentrations in obese subjects can be influenced by caloric restriction. 23 obese human subjects (BMI 44.1 ± 1.1 kg/m(2)) and 12 age- and sex-matched lean controls (BMI 22.3 ± 0.4 kg/m(2)) were included in the study. Obese subjects were treated with a very low-calorie diet (approximately 800 kcal/d) for 12 weeks. Body composition was assessed by impedance analysis, insulin sensitivity was estimated by HOMA-IR and the leptin-to-adiponectin ratio and wnt5a and sFRP5 serum concentrations were measured by ELISA. sFRP5 expression in human adipose tissue biopsies was further determined on protein level by immunohistology. Pro-inflammatory wnt5a was not measurable in any serum sample of lean control subjects. In patients with obesity, however, wnt5a became significantly detectable consistent with low grade inflammation in such subjects. Caloric restriction resulted in a weight loss from 131.9 ± 4.0 to 112.3 ± 3.2 kg in the obese patients group. This was accompanied by a significant decrease of HOMA-IR and leptin-to-adiponectin ratio, indicating improved insulin sensitivity. Interestingly, these metabolic improvements were associated with a significant increase in serum concentrations of the anti-inflammatory factor and wnt5a-inhibitor sFRP5. Obesity is associated with elevated serum levels of pro-inflammatory wnt5a in humans. Furthermore, caloric restriction beneficially affects serum concentrations of anti-inflammatory sFRP5 in such subjects. These findings suggest a novel regulatory system in low grade inflammation in obesity, which can be influenced by nutritional therapy.